Islamic Parenting: Ditinjau dari Perspektif Q.S As-Shaffat Ayat 102 - Nisa Afrinauly Nabila (Jurnal test, 2023)
The rise of events experienced in parenting suggests the importance of knowing parenting styles in caring for and educating children. This study aims to find out how the concept of parenting in Q.S As-Shaffat: 102 can be used as a basis for parenting. The approach in this study uses a qualitative approach, the authors use this approach because they want to explain in detail about Islamic Parenting in Q.S As-Shaffat: 102. This research uses a type of library research. The data in this study came from secondary data sources. Secondary data was collected from various sources such as books and articles on Islamic Parenting in Q.S As-Shaffat: 102. The method of collecting data in this study is by means of documentation, namely research that uses data by analyzing document data, especially in the form of data sources from a number of literature relevant to the research focus. The method of data analysis in this study is the analysis of the listed references. This analysis is carried out to solve the problem being studied. The results of the research are in Q.S As-Shaffat: 102 there is a story of Islamic Parenting from Prophet Ibrahim and his son who can be used as ibrah. There are three important concepts contained in Q.S Ash-Shaffat: 102 in Islamic parenting, namely proper parenting, communication between parents and children, and being open. Recommendations for future research are to look at the implementation of the three Islamic parenting concepts contained in Q.S As-Shaffat: 102 and whether they are still in accordance with today's digital era.